2011
DOI: 10.1016/j.pec.2010.09.018
|View full text |Cite
|
Sign up to set email alerts
|

Self-management problem solving for adolescents with type 1 diabetes: Intervention processes associated with an Internet program

Abstract: Objective-Describe intervention processes associated with an Internet self-management problem solving program for adolescents with type 1 diabetes, and relate participant characteristics to program use.Methods-Forty-one adolescents with type 1 diabetes, aged 13-17, participated in an Internet intervention.Results-Participants reported psychosocial self-management barriers related to social issues (45%), time pressures (22%), and emotions (25%). Most adolescents (76%) completed the two guided problem solving cy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
33
0
2

Year Published

2011
2011
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 45 publications
(37 citation statements)
references
References 30 publications
(21 reference statements)
2
33
0
2
Order By: Relevance
“…For example, females reported greater overall psychosocial barriers, and specifically those related to social support, social situations, and stigma. This is congruent with previous research indicating that girls look to friends for support more often than boys and tend to participate in social networking activities more frequently than boys [23, 28, 50]. Examination of individual profiles allows insight into the nature of the total score, a more efficient use of intervention resources, and may help to maintain adolescent engagement during interventions by directing them to barriers that are most personally relevant.…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…For example, females reported greater overall psychosocial barriers, and specifically those related to social support, social situations, and stigma. This is congruent with previous research indicating that girls look to friends for support more often than boys and tend to participate in social networking activities more frequently than boys [23, 28, 50]. Examination of individual profiles allows insight into the nature of the total score, a more efficient use of intervention resources, and may help to maintain adolescent engagement during interventions by directing them to barriers that are most personally relevant.…”
Section: Discussionsupporting
confidence: 87%
“…Embarrassment and perceived stigma may impact the ability of the individual to communicate needs, seek help, or perform self-care tasks around others. In adolescent diabetes, limited research has documented levels of stigma or the extent to which it impacts self-care [28, 35, 36]. …”
Section: Introductionmentioning
confidence: 99%
“…The latter has been noted in a survey of diabetes educators. They reported that appropriate problem-solving was the most difficult skill to teach patients [23,24]. A large trial in asthmatic adults showed no benefits of problem-solving education, and the authors suggested that patients' lack of motivation to achieve high adherence was the main reason for this failure [25].…”
Section: Discussionmentioning
confidence: 99%
“…‘Sweet Talk’ is a novel intervention designed to support young people with diabetes between clinic visits using text messages sent to a mobile phone 42 43. Furthermore, the use of web based interventions has been shown to increase self-management skills,44 45 enhance education and awareness of community resources,46 act as a novel means of assessing knowledge,47 assist with information transfer48 and enhance peer interaction 41…”
Section: Best Practice In Transitional Carementioning
confidence: 99%